Theatre arts the dynamics of acting - Caltagirone, Dennis 1944-; Snyder, Joan (Lincolnwood, Ill., USA National Textbook, 1997)
Provides an overview of the theatrical production process with a focus on practical acting skills.
Includes index.
Rev. ed. of: The dynamics of acting / Joan Snyder. 3rd ed. c1989.
Keywords: Acting -- Juvenile literature; Acting